Agricultural Extension in the Pluralistic Ecosystem in India - Rohit, Jagriti; C. N, Anshida Beevi; Nagasree, K.; Nirmala, G.; Shankar, K. Ravi (International Journal of Bio-resource and Stress Management, 2017)
Agricultural extension has played a pivotal role in the agricultural development in India. It is turning new leaf every day, adding new dimension to itself. There has been constant evolution of approaches of agricultural extension as it needs to adapt to the new technologies and addressing the complex needs of the diverse clienteles in present changing agricultural scenario. Traditionally, agricultural extension has been associated with transfer of technologies but lately the role of agricultural extension has widened. Besides providing advisory services and technologies, it is now concerned with capacity development, mobilization and sustainability of the farmers and farming community. Decentralization, contracting, privatization, cost recovery, and the involvement of NGOs and farmer-based organizations are some of the major reforms in Extension. Emphasis is now placed on making advisory services demand-driven There was a time when extension services were only provided by the government sector. Slowly, a shift was seen when extension became pluralistic comprising of public, private, cooperatives and NGO’s as well, providing a range of agricultural advisory services and facilitating technology application, transfer and management Now, both public and private extension organization is working in the field for the benefit of the farmers. Pluralistic extension has emerged as paradigm shift in the working of the extension system in India. This paper extensively deals with the changing role and nature or agricultural extension in general and in India in particular.